Sisi, Strategi, dan Substansi : Analisis Strategi Retorik oleh Kandidat Debat Pilkada Bengkulu 2024 berdasarkan Teori Fungsional Benoit - Febran Ihsanudin; Kunto Kunto Adi Wibowo; Ikhsan Ikhsan Fuady; Detta Detta Rahmawan (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
This research analyzes the rhetorical strategies in politics in the Bengkulu 2024 regional election debate according to William L. Benoit's functional theory which classifies campaign messages into three main functions: acclaim, attack, and defense, as well as two content focuses: policy and personal qualities. Quantitative method was used on content analysis through census technique on 1,585 utterances in the debate, this study explains that incumbent candidates tend to use acclaim, while challenger candidates tend to use attack based on functional hypothesis. Policy topics became the core focus rather than character, both by incumbent and challenger candidates. Chi-Square test results show an important relationship between candidate status and the rhetorical strategies and debate topics used. This research shows that local political debates remain focused on content and policy rather than personal conflict, and demonstrates that Benoit's functional theory is appropriate in the Indonesian political context. These results are important for understanding the dynamics of regional political communication and provide a starting point for political actors to design effective campaign strategies.